Beyond solicitousness: a comprehensive review on informal pain-related social support - Bernardes, S. F.; Forgeron, P.; Fournier, K.; Reszel, J. (PAIN, 2017)
Adults with chronic pain cite social support (SS) as an important resource. Research has mostly focused on general SS or pain-specific solicitousness, resulting in a limited understanding of the role of SS in pain experiences. Drawing on SS theoretical models, this review aimed to understand how pain-related SS has been conceptualized and measured and how its relationship with pain experiences has been investigated. Arksey and O´Malley’s scoping review framework guided the study. A database search (2000-2015) was conducted in PsycINFO, CINAHL, MEDLINE, EMBASE using a combination of subject headings/keywords on pain and SS; 3864 citations were screened; 101 full texts were assessed for eligibility; references of 52 papers were hand searched. Fifty-three studies were included. Most studies were either a-theoretical or drew upon the operant conditioning model. There are several self-report measures and observational systems to operationalize pain-related SS. However, the Multidimensional Pain Inventory remains the most often used, accounting for the centrality of the concept of solicitousness in the literature. Most studies focused on individuals with chronic pain (ICPs) self-report of spousal pain-related SS and investigated its main effects on pain outcomes. Only a minority investigated the role of pain SS within the stress and coping process (as a buffer or mediator). Little is known about mediating pathways, contextual modulation of the effectiveness of SS exchanges and there are practically no SS-based intervention studies. Drawing on general SS models, the main gaps in pain-related SS research are discussed and research directions for moving this literature beyond solicitousness are proposed.